Efektivitas FGD (Focus Group Discussion) Cleaning Service Dan Gabungan Cleaning Service Dengan Mahasiswa Dalam Pengelolaan Sampah Plastik Di Poltekkes Kemenkes Padang - Awalia Gusti; Mahaza Mahaza; Lindawati Lindawati (Jurnal Kesehatan Lingkungan, 2020)
The results of a survey conducted at the Poltekkes campus of the Ministry of Health, Padang, found that there were lots of plastic waste scattered about and had not been properly managed. The research was conducted through FGD activities involving students of the Department of Environmental Health with Cleaning Service by measuring the Knowledge, Attitudes and Behavior of Cleaning Service and Students of Semester VII. The number of cleaning services is 31 people. The data analysis was done qualitatively. The results showed that the amount of plastic waste produced at the Poltekkes Kemenkes Padang was an average of 42.33 kg per week. Knowledge Level, Cleaning Service is quite high. have a good attitude. Cleaning Service at Poltekkes Kemenkes Padang has conducted Empowerment in Plastic waste Management by participating in sorting plastic waste and being active as customers at Kesling waste bank. Empowerment of Cleaning Service and Students contributed to the formation of a Waste Bank at Poltekkes. Leaders should provide separate garbage collection places for wet and dry waste. The campus community, especially students, should participate in disposing of garbage according to its type. So that plastic waste can be reused, Kesling Department should provide training for reuse. The leadership's attention is needed to make regulations on reducing plastic waste at the Poltekkes Kemenkes Padang. The formation of a Waste Bank at the Poltekkes of the Ministry of Health in Padang can be an example in other institutions by utilizing cleaning service personnel.